2020
DOI: 10.1021/acsomega.0c04109
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbon Generation Potential and Depositional Setting of Eocene Oil-Prone Coaly Source Rocks in the Xihu Sag, East China Sea Shelf Basin

Abstract: The Xihu Sag in the East China Sea Shelf Basin is a focus for hydrocarbon exploration and development. Hydrocarbons in the Xihu Sag are believed to have mainly originated from coals in the Paleogene Pinghu Formation (shortened as Pinghu coal). In this study, the hydrocarbon generation potential, origin of organic matter, and depositional setting of the Pinghu coal were analyzed by means of optical microscopic analysis, bulk organic geochemistry, and molecular geochemistry analysis. The results reveal that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…The coal and carbonaceous mudstones are characterized by higher HI values (Figure 3a,c), which is commonly observed for coaly samples [69]. The samples with relatively high hydrogen content might be due to high amounts of resinite, as suggested by the abundant diterpanes in the aliphatic fractions (Figure 5) and the maceral composition of other samples taken from this formation [16,23]. The relatively hydrogen-rich nature (Type II/III kerogen) together with maturity at the early to near peak oil window of the samples analyzed suggest that they could be capable of generating some liquid hydrocarbons and significant natural gas at a higher maturity stage [25].…”
Section: Hydrocarbon Generative Potential and Exploration Implicationsmentioning
confidence: 63%
See 1 more Smart Citation
“…The coal and carbonaceous mudstones are characterized by higher HI values (Figure 3a,c), which is commonly observed for coaly samples [69]. The samples with relatively high hydrogen content might be due to high amounts of resinite, as suggested by the abundant diterpanes in the aliphatic fractions (Figure 5) and the maceral composition of other samples taken from this formation [16,23]. The relatively hydrogen-rich nature (Type II/III kerogen) together with maturity at the early to near peak oil window of the samples analyzed suggest that they could be capable of generating some liquid hydrocarbons and significant natural gas at a higher maturity stage [25].…”
Section: Hydrocarbon Generative Potential and Exploration Implicationsmentioning
confidence: 63%
“…Cheng et al [15] compared the geochemical characteristics between a coal and mudstone from the E 2 p and found that they contain predominantly terrigenous source materials with the effect of microbial reworking and were deposited under oxic conditions within an unstratified water column; the mudstone has slightly more algal material input and less oxic conditions during deposition than the coal. Kang et al [16] studied the organic geochemical and petrological characteristics of the coals of the E 2 p. They found that the coals were deposited under relatively oxic peatland conditions (Pr/Ph = 3.33-9.23) with a predominance of terrestrial higher plants input and have entered the hydrocarbon generation threshold. However, a detailed biomarker study on the E 2 p source rocks for elucidating the organic matter source and depositional characteristics changes over time is lacking in the Xihu Sag.…”
Section: Introductionmentioning
confidence: 99%
“…The coal deposits of the Eocene Pinghu Formation in the Xihu Sag in the East China Sea Offshore Basin are perhydrous and vitrinite-rich, like that of the Laisong coals. However, the Pinghu coal deposits contain significantly higher amount of liptinite (1.47-23.02%; Kang et al, 2020) than the Laisong coals. The vitrinite reflectance of the Pinghu coals (0.55-1.28%) is also much higher than the Laisong coal, owing to deeper depth of burial and steeper geothermal gradient in the Xihu Sag (Liu et al, 2020) (Kang et al, 2020).…”
Section: Comparisons With Regional Depositsmentioning
confidence: 90%
“…However, the Pinghu coal deposits contain significantly higher amount of liptinite (1.47-23.02%; Kang et al, 2020) than the Laisong coals. The vitrinite reflectance of the Pinghu coals (0.55-1.28%) is also much higher than the Laisong coal, owing to deeper depth of burial and steeper geothermal gradient in the Xihu Sag (Liu et al, 2020) (Kang et al, 2020). The coal measure of the Oligocene Yacheng Formation is the most important source rock sequence in the Qiongdongnan Basin in the South China Sea region that had entered a phase of mass gas generation, owing to its high degree of thermal evolution and subsidence (Gongcheng et al, 2019).…”
Section: Comparisons With Regional Depositsmentioning
confidence: 90%
“…Key reservoirs and coal seams are present in the late Eocene Pinghu and the Oligocene Huagang formations (Fig. 2), and these also contain the primary coal‐bed source rocks in these two formations (Shen, 2018; Kang et al ., 2020; Liu et al ., 2020a). The Eocene Pinghu Formation, the objective in this study, was deposited during the syn‐rift phase of basin development (Zhou et al ., 2019; Zhu et al ., 2019; Liu et al ., 2020b).…”
Section: Geological Settingmentioning
confidence: 99%